Effect of Technological Waste on Rheological Properties of the Polymer Composite - Dobransky, Jozef; Pollak, Martin; Kocisko, Marek; Torokova, Monika; Kascak, Jakub (Manufacturing Technology Journal, 2021)
The production of automotive products from polymeric materials represents operations associated with the flow of material during its shaping to the desired final mold. The technological aspects of the processing of polymeric materials are closely related to the rheological properties. The article deals with adding technological waste from production to virgin material and its influence on rheological or flow properties of selected polymer composite. The analyzed material is used in the manufacture of components (connectors) in the automotive industry. The rheological properties were measured in two stages. In the first stage, rheological properties were assessed in the short term immediately after preparation of the test samples. In the second stage, half of the samples were exposed to elevated temperature and the effect of aging on the rheological properties of the material was monitored. Based on measured MVR values before exposure to elevated temperature, it can be said that the amount of process waste does not significantly affect the flow properties of the polymer. After exposure to elevated temperature, there is a significant decrease in polymer flow properties probably due to the crystallization of the macromolecular chain.
Keywords: Rheological properties; Composite; Automotive; Technological waste